Contextualized Curriculum with Cultural Relevance for Early Childhood Education in Rural Contexts - Restrepo, Nataly; Correa, Jorge; Taborda, Yor Mary; Ayala, Loredana Joyce (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2023)
The objective of this research was oriented to determine the pedagogical components that configure Comfenalco's educational proposal for early childhood education in the regions of Antioquia-Colombia and relate them to the social and cultural relevance elements. This research is qualitative and is framed within the hermeneutic-interpretative paradigm with systematization of experiences method, supported by discourse analysis. As a result, 3 dimensions are found that give meaning to the contextualized curriculum, related to: (1) presence of what we are in the regions-what characterizes us and gives us identity, (2) practices and knowledge that represent Antioquia regions, and (3) recovering the knowledge and ancestral traditions of the rural contexts in the educational and curricular proposals for early childhood education. It is determined that it is urgent to articulate educational and cultural practices with the history, identity and tradition that are part of the territory, through an educational proposal that contemplates critical interculturality in co-construction with the communities.